Investigation of equivalent dose rate variation in the ground‐level air by Lithuanian highways - Butkus, Donatas; Gaponovienė, Kristina Živilė (Journal of Environmental Engineering and Landscape Management, 2006)
This investigation deals with equivalent dose rate (EDR) of the ground‐level air caused by gamma radiation. Weighting factor for gamma radiation is equal to one, therefore, EDR of the ground‐level air should be similar to the absorbed dose from the ionic radiation dose. In this paper the main parameters which determine the level of equivalent dose rate in the ground‐level air by the Lithuanian highways are defined and analysed. EDR in the ground‐level air by Lithuanian highways was measured and compared to similar average regional values with reference to modeling results evaluating value variation reasons. In the investigation of EDR the ground‐level air was measured in winter and summer. Samples of soil and asphalt were examined with a gamma spectrometer. It was determined that dependence of EDR values in the ground‐level air correlated and depended upon the soil composition, floral or snow cover and distance from an asphalt cover. Cosmic radiation impact on EDR formation is equal at all the locations. Gamma radiation of natural‐origin radionuclides in the soil have the greatest influence on EDR formation in the ground‐level air. The modeling program VISIPLAN was used to define impact of radionuclide radiation from an asphalt cover on EDR formation in a roadside zone. The modeling program InterRAS was used to define EDR formation in the ground‐level air due to gamma radiation of the soil radionuclides. Article in Lithuanian. Lygiavertės dozės galios pažemio ore šalia Lietuvos magistralių matavimo ir modeliavimo rezultatai Santrauka. Nagrinėjama gama spinduliuotės sukelta lygiavertės dozės galia (LDG) pažemio ore. Gama spinduliuotės svorinis daugiklis lygus vienetui, taigi LDG pažemio ore tapati sugertosios dozės galiai. Straipsnyje įvardyti ir išanalizuoti pagrindiniai parametrai, lemiantys LDG pažemio ore šalia Lietuvos magistralių. Nustatytosios LDG pažemio ore šalia Lietuvos magistralių vertės palygintos su modeliavimo rezultatais, įvertintos verčių kaitos priežastys. Ekspedicijų metu žiemą ir vasarą nustatytos LDG pažemio ore vertės šalia magistralių pasirinktose vietovėse. Atlikti dirvožemio bei asfalto mėginių gama spektrometriniai tyrimai. Nustatyta, kad LDG pažemio ore vertės priklauso nuo dirvožemio sudėties, augalijos ar sniego dangos bei atstumo nuo asfalto dangos. Didžiausios įtakos turi dirvožemyje esančių gamtinės kilmės radionuklidų gama spinduliuotė. Modeliavimo programa VISIPLAN nustatyta radionuklidų, esančių asfalto dangoje, spinduliuotės įtaka LDG formavimuisi pakelės zonoje. Modeliavimo programa InterRAS nustatyta LDG pažemio ore, lemiama dirvožemyje esančių radionuklidų spinduliuotės. Reikšminiai žodžiai: lygiavertė dozės galia (LDG) pažemio ore, gama spinduliuotė, radionuklidas, gama spektrometriniai tyrimai, modeliavimo programos VISIPLAN ir InterRAS. First Published Online: 14 Oct 2010